Evaluation of cowpea (Vigna unguiculata (L.) Walp.) germplasm lines for tolerance to drought - Fatokun, C.A.; Boukar, O.; Muranaka S (Cambridge University Press, 2012)
Cowpea is an important grain legume crop in sub-Saharan Africa (SSA) where, on a worldwide basis, the bulk is produced and consumed. The dry savanna area of SSA is where cowpea is mostly grown under rain-fed conditions. The crop is therefore prone to drought which may occur early, mid and/or late in the cropping season. Compared with many other crops, cowpea is drought tolerant, even though drought is still a major constraint limiting its productivity in SSA. Increasing the level of drought tolerance in existing cowpea varieties grown by farmers would enable them to obtain more and stable yield from their cowpea fields. As a first step towards enhancing drought tolerance in existing cowpea varieties, 1288 lines were selected randomly from cowpea germplasm collections maintained at the International Institute of Tropical Agriculture, and evaluated for their drought tolerance at Ibadan. Drought was imposed by withdrawal of irrigation from 5 weeks after sowing. On average, drought reduced the number of days to flower by 12 d, and the mean grain yield per plant was also reduced by 67.28%. A few of the cowpea lines stayed green for up to 6 weeks after irrigation was stopped, even though some of these produced no pods when the study was terminated. Further evaluation in the screenhouse of 142 selected drought-tolerant lines helped to identify six lines that could be potential parents for developing breeding lines with enhanced drought tolerance.